A comparative study of culture methods and polymerase chain reaction for Salmonella detection in egg content - Soria, Mario; Soria, Maria Cecilia; Bueno, Dante Javier (Oxford Academic Press, 2019)
The present work compared 2 culture methods and a PCR assay applied with 2 enrichment methods for the detection of motile and nonmotile Salmonella strains using artificially contaminated egg content. The specificity (Sp) was 1 in all methods. The sensitivity (Se), accuracy (Ac), positive predictive value (PPV), and negative predictive value (NPV) were 1 in both culture methods for motile and nonmotile strains. In reference to the PCR methods, Se and PPV were between 0 and 1, whereas Ac and NPV were between 0.14 and 1. The detection level of motile and nonmotile strains was 5 to 54 cfu per 25 mL for both culture methods, but some strains could not be detected by the PCR methods. Extending incubation time of the enrichment medium to 5 d in the tetrathionate broth (TT), and Muller-Kauffmann tetrathionate-novobiocin broth (MKTTn) methods did not improve the isolation rates. All selective plating media did not show any statistical differences in the parameters of performance studied. Kappa coefficients showed that there was an excellent agreement between the bacteriological methods for all Salmonella strains. The agreement was very good and good between the PCR methods, for motile and nonmotile strains, respectively. However, there was a poor agreement when the PCR and bacteriological methods were compared for motile and nonmotile Salmonella strains. The TT and MKTTn methods are similar in terms of Ac, Se, Sp, PPV, and NPV for different Salmonella strains in egg content. The use of the PCR method cannot improve the same parameters, described before, in this matrix. So, further studies are needed to improve the performance parameters and limit of detection in egg content for the PCR methods, so that test can be used in poultry and food industry.